Simulasi Gaya Pemotongan pada Proses Bubut dengan Software Third Wave Advantedge - Qoryah, Rika Dwi Hidayatul; Sari, Herninda Ayu Meylinda; Darsin, Mahros; Mulyadi, Santoso (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
The cutting force that reacts to cutting tool and workpieces will result deflection. Deflection is the cause of product deviation and vibration sources that can shorten the life of the cutting tool. Simulation of machining process is carried out to get an estimate of cutting force in some machining process conditions., then compare it to the experiments. The research aims to find out the influence of spindle rotary speed, feed rate and depth of cut on cutting forces in turning process with cutting tool HSS and workpiece Al 6061. This research uses three-dimensional simulation method using Third Wave AdvantEdge software. Following by comparison between the simulation with the experiments results. The simulation was in accordance to the experiments in term of the magnitude of the forces, from the biggest they are tangential, axial, and radial force respectively. Cutting force will decrease with increased spindle turning speed. Cutting force will increase with the rising feed rate and depth of cut. However, the simalution still highly deviate from the experiments at the rate of 71%, 44.3%, and 21.3% for axial, radial and tangential forces respectively. The possible cause of these high errors relates to forces measuring method in experiments.